2004
DOI: 10.1074/jbc.m310976200
|View full text |Cite
|
Sign up to set email alerts
|

Munc-18-1 Inhibits Phospholipase D Activity by Direct Interaction in an Epidermal Growth Factor-reversible Manner

Abstract: Mammalian phospholipase D (PLD) has been reported to be a key enzyme for epidermal growth factor (EGF)-induced cellular signaling, however, the regulatory mechanism of PLD is still unclear. In this report, we found that Munc-18-1 is a potent negative regulator of PLD in the basal state and that its inhibition is abolished by EGF stimulation. We investigated PLD-binding proteins obtained from rat brain extract, and identified a 67-kDa protein as Munc-18-1 by peptide-mass fingerprinting. The direct association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…However, the roles of these inhibitors in signal-dependent PLD activity has not been demonstrated. Recently our group reported that Munc-18-1 directly inhibits PLD activity (53). In this report, epidermal growth factor treatment was found to trigger the dissociation of Munc-18-1 from PLD, and the inhibitory role of Munc-18-1 upon basal PLD activity, in a signaldependent manner, was suggested.…”
Section: Figmentioning
confidence: 69%
“…However, the roles of these inhibitors in signal-dependent PLD activity has not been demonstrated. Recently our group reported that Munc-18-1 directly inhibits PLD activity (53). In this report, epidermal growth factor treatment was found to trigger the dissociation of Munc-18-1 from PLD, and the inhibitory role of Munc-18-1 upon basal PLD activity, in a signaldependent manner, was suggested.…”
Section: Figmentioning
confidence: 69%
“…PLD has a large role in the activity of lipid hydrolysis, and until now there have been many reports that its activity is elaborately controlled by many cellular regulators in diverse cell systems (20,22,26,31,33,34,35,37,50). In contrast, little is known about the details of mechanisms in the regulation of other proteins by PLD through direct binding.…”
Section: Discussionmentioning
confidence: 98%
“…23,32,33,[44][45][46][47][48] However, less is known about the interactions of PLD with downstream signaling proteins that would account for its presumed roles in regulating cell function. Here we present evidence that PLD2 complexes with Syk and in doing so facilitates activation of mast cells in the manner depicted in Figure 7D.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the PLD PX and PH domains have been implicated in the direct interaction of PLD, particularly PLD2, with other proteins in a lipase-independent manner. These proteins include PLC␥, 32 Munc-18-1, 33 and PKC. 34 It has also been reported that PLD and c-Src interact similarly but in a lipase-dependent manner to enable phosphorylation of PLD2 and activation of Src.…”
Section: Introductionmentioning
confidence: 99%